2017
DOI: 10.1038/srep42914
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 4D polymorphisms associate with the short-term outcome in ischemic stroke

Abstract: It has been demonstrated that phosphodiesterase 4D (PDE4D) genetic polymorphism is associated with ischemic stroke. However, the association between PDE4D gene and prognosis after ischemic stroke remains unknown. We consecutively enrolled ischemic stroke patients admitted to Beijing Tiantan Hospital from October 2009 to December 2013. Clinical, laboratory and imaging data upon admission were collected. All patients were followed up 3 months after stroke onset. Odds ratios (ORs) and 95% confidence intervals (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Subsequently, several studies have demonstrated a positive association between IS and rs966221 in PDE4D , 16,17 and a meta‐analysis has confirmed this association 18 . Recently, Song et al 19 . reported that rs966221 within PDE4D was associated with increased risk of a poor outcome 3 months post‐stroke.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, several studies have demonstrated a positive association between IS and rs966221 in PDE4D , 16,17 and a meta‐analysis has confirmed this association 18 . Recently, Song et al 19 . reported that rs966221 within PDE4D was associated with increased risk of a poor outcome 3 months post‐stroke.…”
Section: Discussionmentioning
confidence: 95%
“…The PDE4 gene family consists of four subtypes (PDE4A-D) and more than 20 splice variants (18). PDE4D is located in chromosome 5q12 and encodes cAMP-specific 3',5'-cyclic phosphodiesterase 4D (19). PDE4D mRNA is mainly expressed in the emetic center of the mouse hippocampus (such as the nucleus tractus solitarius), but it is upregulated after CUMS mode (20).…”
Section: Discussionmentioning
confidence: 99%
“…Third, although the association of variants with TBXAS1 transcripts level in platelets was demonstrated, the protein level of TBXAS1 was not measured in this study; moreover, testing the protein level of TBXAS1 in platelets and investigating the SNPs effect on promoter activity by luciferase assay can reveal more details about the SNPs effect on TBXAS1 promoter activity. Finally, undoubtedly IS is the complex multifactorial disorder believed to be the result of an interaction between the genetic background of an individual and various environmental factors . Although we have identified the association between TBXAS1 SNPs and their haplotypes and the risk of LAA stroke, many environmental and genetic factors and their interactions remained unmeasured.…”
Section: Discussionmentioning
confidence: 99%